Slow excitatory post-synaptic currents in bull-frog sympathetic neurones. - Akasu, T (1984)
Electrogenesis of the slow excitatory post-synaptic current (slow e.p.s.c.) was analysed with voltage-clamp methods in curarized sympathetic ganglion cells of bull-frogs. Three types of slow e.p.s.c. were observed from B neurones of sympathetic ganglia. The type I slow e.p.s.c. was associated with a decrease in membrane conductance, was depressed by membrane hyperpolarization and nullified at -60 to -70 mV. It was observed in 65% of the sympathetic neurones studied. The type II slow e.p.s.c. was associated with an increase in membrane conductance, was depressed by membrane depolarization and nullified at around +5 mV. It was observed in 14% of the neurones studied. A third type of slow e.p.s.c. was recorded from 21% of the sympathetic neurones in this study. This slow e.p.s.c. was a mixed type having characteristics of both type I and type II slow e.p.s.c.s. Activation of muscarinic cholinergic receptors by application of acetylcholine (ACh) also produced two types of inward currents. The nature of each type of muscarinic slow ACh current was similar to that of each type of slow e.p.s.c. The time course of the falling phase of type I and type II slow e.p.s.c.s was dependent on the membrane potential. The type I slow e.p.s.c. was primarily dependent on extracellular K+ and appeared to be produced by a suppression of the M-current (Brown & Adams, 1980). The type II slow e.p.s.c. was due to an increased conductance, probably to Na+, and other cations.